2016
DOI: 10.3389/fnhum.2016.00607
|View full text |Cite
|
Sign up to set email alerts
|

The Time-Course of Acute Changes in Corticospinal Excitability, Intra-Cortical Inhibition and Facilitation Following a Single-Session Heavy Strength Training of the Biceps Brachii

Abstract: Objective: The current understanding of acute neurophysiological responses to resistance training remains unclear. Therefore, we aimed to compare the time-course of acute corticospinal responses following a single-session heavy strength training (HST) of the biceps brachii (BB) muscle and provide quantifiable evidence based on the super-compensation model in an applied setting.Methods: Fourteen participants completed a counter-balanced, cross-over study that consisted of a single HST session (5 sets × 3 repeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
25
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 37 publications
(53 reference statements)
7
25
1
Order By: Relevance
“…In fact, chronic ST tends to decrease short‐interval intracortical inhibition (SICI) and silent period (SP) duration, suggesting that a release of intracortical inhibition could be one mechanism underlying the chronic increases in cM1 excitability and in the effectiveness of the motor command to increase MVC force. However, the time course of such adaptations is unclear because results from acute studies are inconsistent . In addition to reductions in SICI or SP, an increase in intracortical facilitation (ICF) could also contribute to the increase in CSE.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In fact, chronic ST tends to decrease short‐interval intracortical inhibition (SICI) and silent period (SP) duration, suggesting that a release of intracortical inhibition could be one mechanism underlying the chronic increases in cM1 excitability and in the effectiveness of the motor command to increase MVC force. However, the time course of such adaptations is unclear because results from acute studies are inconsistent . In addition to reductions in SICI or SP, an increase in intracortical facilitation (ICF) could also contribute to the increase in CSE.…”
Section: Introductionmentioning
confidence: 99%
“…ICF is thought to involve corticocortical pyramidal cells with glutaminergic synapses projecting to the cortical neurons that activate the corticospinal tract . However, little is known about changes in ICF after an acute session of ST, with two studies showing little or no changes …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This may suggest that changes in CSE are similar for skill training and strength training (26). Conversely, other studies have suggested that resistance training is associated with a decrease in the size of motor-evoked potentials (MEPs) (33, 34), however, the conclusions may depend on the timing of the CSE testing relative to the end of training (34). In persons with tetraplegia, there are surprisingly few studies of progressive resistance training (without concurrent functional electrical stimulation) directed at improving strength in the paretic muscles.…”
Section: Introductionmentioning
confidence: 97%